(untitled) (Research, Society and Development, 2020)
This study had the contribution of the nursing consultation in prenatal care. This qualitative study was conducted in a municipality in the southwestern state of Paraná, Brazil. Seven nurses participated in prenatal care in the basic network of the municipality. Participant observation and semi-structured interviews were used. The data were analyzed through the operative proposal. The nursing consultation in prenatal care requires technical-scientific knowledge, involvement and commitment of the professional. Although health education groups were established in the routine of care for pregnant women, in nursing consultations these actions were more frequent, revealing one of the contributions of the nursing consultation in prenatal care. The insertion of nurses in prenatal care, through nursing consultation, enables the implementation of a care model, focused on integrality of women’s health care.